2020
DOI: 10.1080/15205436.2020.1817943
|View full text |Cite
|
Sign up to set email alerts
|

Me, Myself, and My Favorite Media Figure: An Objectification Perspective on the Role of Media and Peers in Early Adolescents’ Self-sexualization

Abstract: Me, myself, and my favorite media figure: An objectification perspective on the role of media and peers in early adolescents' selfsexualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
3
7
0
Order By: Relevance
“…Furthermore, the study revealed that appearance motivation from social media influences the internalization of an ideal thin appearance, and this result is in line with Trekels and Eggermont [36], where attractive appearance in the media has standards, such as that women must be young, thin, and sexy. When the message reaches individuals, they will become motivated and change their appearance to make it look better [36].…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Furthermore, the study revealed that appearance motivation from social media influences the internalization of an ideal thin appearance, and this result is in line with Trekels and Eggermont [36], where attractive appearance in the media has standards, such as that women must be young, thin, and sexy. When the message reaches individuals, they will become motivated and change their appearance to make it look better [36].…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, the study revealed that appearance motivation from social media influences the internalization of an ideal thin appearance, and this result is in line with Trekels and Eggermont [36], where attractive appearance in the media has standards, such as that women must be young, thin, and sexy. When the message reaches individuals, they will become motivated and change their appearance to make it look better [36]. Furthermore, the results of this hypothesis are strengthened by the results of qualitative interviews, which explain that respondents are motivated after watching content that promotes better physical appearance, such as exercise and a healthy lifestyle: "Feel motivated to look more attractive when viewing makeup, skincare, or sports content" (Interviewee 5) and "Ever motivated after seeing only gym content but wasn't interested in looking thin like a model" (Interviewee 1).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations